Pesquisa de novos antibióticos anti-Pseudomonas aeuruginosa utilizando métodos in silico - Daniel, Cristiane (2020)
Hospital infection is a serious public health problem, as it increases the time and costs of hospitalizations and leads to increased rates of morbidity and mortality in patients. Antibiotics, which are less and less potentially active, limit the treatment options for these infections, with the increasing need for the development of new drugs and new classes of antibiotics. Infections caused by P. aeruginosa are classified as the third most frequent pathogen to resistance and finding an effective treatment against them is a challenge, since the concentrations capable of inhibiting resistance and becoming active against the bacteria are incompatible with human exposure. In this context, using alternatives that circumvent the resistance of this bacterium has been a good option to eradicate the infection, the inactivation of enzymes that have the capacity to confer such resistance would be one of them. Thus, molecular modeling has proven to be one of the most important tools in the discovery of these new drugs, as it has the potential to achieve intrinsic properties that favor specific interactions. The objective of this project was to carry out QSAR studies for a set of compounds derived from benzamidobenzoic acid that showed the ability to inhibit the PqsD activity of P. aeruginosa in vitro, and from this set to define a pharmacophoric model, to use as a screening tool in the identification of new compounds with potential for antimicrobial activity. Materials and methods: a data set formed by structures containing benzamidobenzoic acid as an essential pharmacophore, previously described in the literature, using molecular modeling tools, thermodynamically stable geometries were defined and used to obtain a series of molecular descriptors, these used for 2D-QSAR studies. These same structures were also used as a basis for pharmacophoric modeling for virtual screening. The model obtained in the QSAR was validated as currently recommended by the literature. Molecular anchorage studied, in silico toxicology were used as part of the study aiming to find new potentially successful compounds as a starting point for the development of new antibiotics for the treatment of infections caused by the bacteria under study. This work obtained 12 compounds, of which 10 are promising compound-prototypes for the planning of new P. aeruginosa PqsD inhibitors, an initial step for the development of new antibiotic agents.